Immediate clinical outcomes of left bundle branch area pacing vs conventional right ventricular pacing - Zhang, JunMeng; Wang, Zefeng; Cheng, Liting; Zu, Linna; Liang, Zhuo; Hang, Fei; Wang, Xinlu; Li, Xiaoyan; Su, Ruijuan; Du, Jie; Wu, Yongquan (Clinical cardiology (Mahwah, N.J.), 2019)
Background Left bundle branch area pacing (LBBaP) is a new physiological pacing strategy that produces comparable clinical effects to His bundle pacing (HBP). Objective The purpose of this study was to investigate the immediate clinical outcomes of LBBaP vs RVP. Methods and Results From April 2018 to September 2018, we included 44 patients under continuous pacemaker implantation. Patients were randomly divided into the LBBaP group and conventional RVP group. Compared to the RVP group, the LBBaP group displayed significantly increased operative (90.10 ± 19.68 minutes vs 61.57 ± 6.62 minutes, P < .001) and X‐ray exposure times (15.55 ± 5.62 minutes vs 4.67 ± 2.06 minutes, P < .001). The lead threshold of the LBBaP group was increased (0.68 ± 0.20 mV vs 0.51 ± 0.0 mV, P = .001), while the R‐wave amplitude and ventricular impedance did not significantly differ between the two groups. The conventional RVP procedure significantly widened the QRS complex (93.62 ± 8.28 ms vs 135.19 ± 12.21 ms, P = .001), whereas the LBBaP had no effect on QRS complex (130.13 ± 43.30 ms vs 112.63 ± 12.14 ms, P = .904). Furthermore, the LBBaP procedure significantly narrowed the QRS complex in patients with left bundle branch block (LBBB) (168.43 ± 38.870 ms vs 119.86 ± 6.69 ms, P = .019). Conclusion LBBaP is a new physiological, safe and effective pacing procedure with a high overall success rate. Compared to conventional RVP, LBBaP can correct LBBB, thereby improving cardiac electrical dyssynchrony.